Suggestions for teaching floating, sinking and density - Taylor, Neil; Taylor, Subhashni; Rizk, Nadya; Cooper, Grant (2017)
Understanding the concept of density is crucial to enabling students to explain the phenomena of floating and sinking. However, density is not an easy concept for students to understand, not least because as Dawkins, Dickerson, McKinney and Butler (2008) argue, the use of floating and sinking demonstrations in determining density pays little attention to the idea that many objects do not have uniform density. Obvious examples are air-filled, hollow objects. Dawkins et al. and Roach (2001) have reported on the problems pre-service teachers in the USA encounter with the concept of density, despite it being covered in high school chemistry and physics text books. This article describes a teaching sequence used with preservice primary teachers in Australia that helps them explain floating and sinking by applying the concept of density appropriately. Some of the teaching ideas may also be useful for teaching at the middle school level. The sequence is presented in narrative form rather than as a formal lesson plan.